Genetic Variants in DNA Repair Pathways as Potential Biomarkers in Predicting Treatment Outcome of Intraperitoneal Chemotherapy in Patients With Colorectal Peritoneal Metastasis: A Systematic Review - Hulshof, Emma C.; Lim, Lifani; de Hingh, Ignace H. J. T.; Gelderblom, Hans; Guchelaar, Henk-Jan; Deenen, Maarten J. (Frontiers in Pharmacology, 2020)
Background: The introduction of cytoreductive surgery (CRS) followed by hyperthermic intraperitoneal chemotherapy (HIPEC) with either oxaliplatin or mitomycin C for patients with colorectal peritoneal metastasis (CPM) has resulted in a major increase in overall survival. Nonetheless, despite critical patient selection, the majority of patients will develop recurrent disease within one year following CRS+HIPEC. Therefore, improvement of patient and treatment selection is needed and may be achieved by the incorporation of genetic biomarkers. This systematic review aims to provide an overview of genetic biomarkers in the DNA repair pathway that are potentially predictive for treatment outcome of patients with colorectal peritoneal metastases treated with CRS+HIPEC with oxaliplatin or mitomycin C. Methods: A systematic review was conducted according to the PRISMA guidelines. Given the limited number of genetic association studies of intraperitoneal mitomycin C and oxaliplatin in patients with CPM, we expanded the review and extrapolated the data from biomarker studies conducted in colorectal cancer patients treated with systemic mitomycin C and oxaliplatin-based chemotherapy. Results: In total, 43 papers were included in this review. No study reported potential pharmacogenomic biomarkers in patients with colorectal cancer undergoing mitomycin c-based chemotherapy. For oxaliplatin-based chemotherapy, a total of 26 genetic biomarkers within 14 genes were identified that were signiﬁcantly associated with treatment outcome. The most promising genetic biomarkers were ERCC1 rs11615, XPC rs1043953, XPD rs13181, XPG rs17655, MNAT rs3783819/ rs973063/rs4151330, MMR status, ATM protein expression, HIC1 tandem repeat D17S5 and PIN1 rs2233678. Conclusion: Several genetic biomarkers have proven predictive value for the treatment outcome of systemically administered oxaliplatin. By extrapolation, these genetic biomarkers may also be predictive for the efficacy of intraperitoneal oxaliplatin. This should be the subject of further investigation.